Design and development of a tabletop indoor herb or vegetable planter box - Lee, Jacob Zong Wei (Nanyang Technological University, 2022)
Singapore is a country known for importing most of their food with over 90% imported. However, the past few years has taught us that food security is something that can be changed drastically quickly. From lockdown restrictions thru COVID 19 to war breaking out between Russia and Ukraine, it has hindered the global food exports and affected us. This highlights the importance to strengthen our local food production. In addition, land space in Singapore is limited and not much area can be used for companies to grow local produces. Area used in housing is the highest which can be a solution to increase food production. In this project, we will be looking at the current innovation and technologies available in indoor planting and ways we could improve in them to fit into our everyday lives. With the usage of sensors and processors plus data to analyze plant growth.